Psychological Aspects of Poverty Alleviation in the Qur'an; Discourse on the Role of the Government and BAZNAZ - Choirur Rois; Zulkifli zul; Ali Wafa (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2023)
Qur'an takes seriously the issue of poverty alleviation. Hence, the Government and BAZNAS also prioritize poverty alleviation with various efforts and programs. According to Statistics Indonesia or Badan Pusat Statistic (BPS), the percentage of Indonesia's poverty population in one year (March 2020-March 2021) increased by 0.36% or as many as 1,120,000 people. According to this issue, BAZNAS successfully alleviates poverty by 28,859 people within one year. The data shows the lack of absorption of poverty alleviation programs in Indonesia. This research aims to investigate how government and BAZNAS alleviate poverty in Indonesia. This investigation uses a qualitative approach with literature studies and descriptive analysis techniques. This present study also identifies the solutions in the Qur'an to the government and BAZNAS in alleviating poverty. Based on the analysis, the findings in this study indicate that the role of the government and BAZNAS in alleviating poverty has not been integrated. The achievements obtained are less than optimal and tend to be ineffective. Qur'an offered three psychological solutions; mental reconstruction in alleviating natural poverty, collective philanthropic movements in alleviating cultural poverty, and harmonization of government programs and BAZNAS in alleviating structural poverty.